General Purpose Mobile Robot - Yazan, Hamdan; Yousef, AbuSada (My University, 2017)
Fully-autonomous mobile robots are one of the most researched subject at the moment. It involves many aspects of engineering and computer science. This thesis details the development the hardware and control system of two-wheeled differential drive system that autonomously regulates its position, heading and velocity based on feedback from optical encoder, ultrasonic sensors and 9DOF accelerometer-magnetometer-gyroscope module. This project is very important on the research level, where it achieves many goals required –or aspired- in todays and tomorrows visions. Also, it is important for the students’ practice of research and development of a project that involves multiple aspects of today’s technical society. The project is a basis for many sophisticated projects that can be built on or integrated with. Finally, it is aspired that this project would be a wide window for the developers to be involved in deeper understanding and experience of today’s technical society and the many specializations that can be involved in in light of this project.